Mesenchymal Progenitors Derived from Different Locations in Long Bones Display Diverse Characteristics - Weiguang Lu; Bo Gao; Jing Fan; Pengzhen Cheng; Yaqian Hu; Qiang Jie; Zhuojing Luo; Liu Yang (Hindawi Limited, 2019)
Mesenchymal progenitors within bone marrow have multiple differentiation potential and play an essential role in the maintenance of adult skeleton homeostasis. Mesenchymal progenitors located in bone regions other than the bone marrow also display bone-forming properties. However, owing to the differences in each distinct microenvironment, the mesenchymal characteristics of skeletal progenitor cells within different regions of long bones may show some differences. In order to clearly elucidate these differences, we performed a comparative study on mesenchymal progenitors from different regions of long bones. Here, we isolated mesenchymal progenitors from the periosteum, endosteum, and bone marrow of rat long bones. The three groups exhibited similar cellular morphologies and expressed the typical surface markers associated with mesenchymal stem cells. Interestingly, after cell proliferation assays and bidirectional differentiation analysis, periosteal mesenchymal progenitors showed a higher proliferative ability and adipogenic differentiation potential. In contrast, endosteal mesenchymal progenitors were more prone to osteogenic differentiation. Using in vitro osteoclast culture systems, conditioned media from different mesenchymal progenitor cultures were used to induce osteoclastic differentiation. Osteoclast formation was found to be significantly promoted by the secretion of RANKL and IL-6 by endosteal progenitors. Overall, our results provide strong evidence for the importance of selecting the appropriate source of skeletal progenitors for applications in future skeleton regeneration therapies.